The Use of Facial Characteristics as Engendering Strategies in Phoenician-Punic Studies - López-Bertran, Mireia (Near Eastern archaeology, 2016)
Facial characteristics such as discs on cheeks or exaggerated chins have been traditionally used to interpret Phoenician-Punic materials as representing either females or males. Beards and pointed chins, for instance, have been considered male attributes for terracotta masks, while disks have been interpreted as feminine makeup when present on figurines and ostrich eggshells. However, problems and even paradoxes of interpretation emerge when such characteristics appear on objects already (and perhaps arbitrarily) alternately gendered male or female. Thus, the cosmetic disks on “feminine” figurines become “warts” and “astral symbols” when appearing on “male” masks. Such conundrums show how slippery and contradictory engendering objects using facial characteristics might be, and cast doubt on the gender assignment of the objects themselves. In this article we analyze a sample of Phoenician-Punic materials from the Western Mediterranean (Iberia, Ibiza, Carthage, Sicily, and Sardinia) dated between the seventh and the third centuries B.C.E. with an eye towards such engendering strategies.